The application of value management at briefing stage of refurbishment work : case study : refurbishment unit, Property Department Pejabat Harta Bina - 421860 Masnizah Osman (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah ) - Universiti Teknologi Malaysia, 2007